Microprocessor-programmed infusion of theophylline rapidly attained expected steady-state level in rabbit plasma - Duan Shi-ming; Xu Xun; Ye Miao; Fu Ying (Acta Pharmacologica Sinica, 2016)
A self-made microprocessor-programmed (two-compartmental model) infusion controller was connected with an infusion pump, which achieved an expected steady-state plasma concentration (Cpss) rapidly (5 T1(2)alpha) and maintained the level. Theophylline was selected as an example, and its pharmacokinetic parameters of rabbits, expected Cpss, body weight (wt), and infusion time (t) were input. The programmed infusion rate (Kt) was determined by the following equation: (Kt) = Cpss.K10.Vc.wt (1 + [(K21-beta)/beta]EXP(-K21t)) and the predicted value was calculated by the formula: C(t) = Cpss X [1-EXP(-alpha t)]. The needed concentration and total volume of drug were automatically shown on the screen. The drug was automatically infused after pumping, and the plasma concentration of theophylline was measured by colorimetric method. The results showed that the median absolute value of the performance error (MAVPE) was 8.3%. Although T1(2)beta of theophylline was 6.08 h, the expected Cpss was attained in only 30 min (5 T1(2)alpha) after start of infusion and then well maintained.